2015
DOI: 10.3389/fphys.2015.00028
|View full text |Cite
|
Sign up to set email alerts
|

From two competing oscillators to one coupled-clock pacemaker cell system

Abstract: At the beginning of this century, debates regarding “what are the main control mechanisms that ignite the action potential (AP) in heart pacemaker cells” dominated the electrophysiology field. The original theory which prevailed for over 50 years had advocated that the ensemble of surface membrane ion channels (i.e., “M-clock”) is sufficient to ignite rhythmic APs. However, more recent experimental evidence in a variety of mammals has shown that the sarcoplasmic reticulum (SR) acts as a “Ca2+-clock” rhythmical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 62 publications
4
87
1
1
Order By: Relevance
“…One limitation is that our current study focused on regulating cellular automaticity by the sarcolemmal currents of I K1 -induced I f activation but didn’t include the influence of intracellular Ca 2+ transients, which coordinates together with sarcolemmal ion currents to control cellular automaticity 49,50 . Recently, Vaidyanathan et al found that upregulated I K1 could enhance the amplitude of Ca 2+ transients in iPSC-CMs 51 ; therefore, the automaticity development promoted by I K1 -induced I f activation might be also mediated partially through intracellular Ca 2+ transients.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation is that our current study focused on regulating cellular automaticity by the sarcolemmal currents of I K1 -induced I f activation but didn’t include the influence of intracellular Ca 2+ transients, which coordinates together with sarcolemmal ion currents to control cellular automaticity 49,50 . Recently, Vaidyanathan et al found that upregulated I K1 could enhance the amplitude of Ca 2+ transients in iPSC-CMs 51 ; therefore, the automaticity development promoted by I K1 -induced I f activation might be also mediated partially through intracellular Ca 2+ transients.…”
Section: Discussionmentioning
confidence: 99%
“…This process activates a current generated by the sodium–calcium exchanger, which contributes to diastolic depolarization (“calcium clock”), ultimately triggering action potential firing 42. Although there is debate whether one of these “clock” mechanisms is the key initiator of diastolic depolarization and cardiac pacemaking,43 a close interplay between both concepts (“coupled clock”) seems to be crucial for proper rhythm generation in pacemaker cells 44…”
Section: Ivabradine – Mode Of Action and Pharmacologymentioning
confidence: 99%
“…Involvement of intracellular Ca 2+ cycling in Ca 2+ wave formation and resultant DADs in Purkinje cells was also discussed 17 but the role of intracellular Ca 2+ cycling in pacemaker function of both normal canine Purkinje and SAN cells remains uncertain. Is there an interdependence of I f and Ca 2+ cycling (so called membrane and Ca 2+ clocks 19 ) in these pacemakers of the heart?…”
Section: Introductionmentioning
confidence: 99%